Practical military ordnance identification - Gersbeck, Tom (CRC Press/Taylor & Francis Group, 2019)
The focus of Practical Military Ordnance Identification, Second Edition is the application of a practical deductive process to identify unknown ordnance items that are commonly recovered outside military control. Coverage new to this edition include: a list of conventional markings; additional safety precautions to take; an expanded list of high explosives; additional technical details on explosives effects; hazards associated with pyrotechnics, pyrophorics, smoke compounds, and incendiaries; a section on pre-1870 projectiles, hand grenades, landmines, underwater ordnances, and rockets; and details on Man-Portable-Air-Defense-Systems (MANPADS) missile systems.